Low-Phytotoxic Deep Eutectic Systems as Alternative Extraction Media for the Recovery of Chitin from Brown Crab Shells - Rodrigues, Liliana A. (2021)
MultiBiorefinery—POCI-01-0145-FEDER-016403 ERC-2016-CoG 725034 COST Action CA18224